2021
DOI: 10.1186/s13089-021-00206-w
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of implementing a longitudinal curriculum in undergraduate medical education: The wake forest experience

Abstract: Background Hands-on ultrasound experience has become a desirable component for undergraduate medical education (UGME) curricula throughout medical schools in the United States (US) to enhance readiness for future training. Ultrasound integration can be a useful assistive educational method in undergraduate medical education to improve anatomy and physiology skills. Relatively few medical schools have integrated ultrasound experiences formally into their 4-year medical school curriculum due to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Several reports indicate that medical schools in North America [ 107 , 130 , 131 ], Europe [ 132 , 133 ], and Asia [ 134 ] continue to integrate ultrasound into undergraduate medical curricula. A survey conducted in 2019 showed that 74% of 64 responding US medical schools had integrated ultrasound into basic science courses, 66% into practice of medicine/clinical skills courses, and 35% into clinical rotations [ 130 ].…”
Section: Vertical Curriculummentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports indicate that medical schools in North America [ 107 , 130 , 131 ], Europe [ 132 , 133 ], and Asia [ 134 ] continue to integrate ultrasound into undergraduate medical curricula. A survey conducted in 2019 showed that 74% of 64 responding US medical schools had integrated ultrasound into basic science courses, 66% into practice of medicine/clinical skills courses, and 35% into clinical rotations [ 130 ].…”
Section: Vertical Curriculummentioning
confidence: 99%
“…Many schools have likely incorporated or are trying to incorporate ultrasound into 1 or 2 years of undergraduate medical education. However, vertical or longitudinal 4-year curricula are being integrated gradually among North American medical schools [ 8 , 131 ].…”
Section: Vertical Curriculummentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Medical school ultrasound curriculums have begun implementing clinical applications including the Wake Forest University. 13 The quantity and complexity of content had importance because overwhelming medical student cognitive load would result in inattention. 14 With a near peer approach to the workshop, there was less likelihood of a blind expert spot phenomenon, which can result in cognitive overload.…”
Section: Keys To An Impactful Workhop For Medical Studentsmentioning
confidence: 99%